STUDENTS 'TRAINING OF THE PHYSICO-MATHEMATICAL PROFILE OF THE METHODS OF THE METHODS USING THE INTEGRATED ENVIRONMENT OF WORD AND MATLAB - Doroshenko M. (Kherson State University, 2018)
The article discusses the possibilities of using the integrated Word and Matlab environment for training students of the physics and mathematical profile of computing methods. This discipline plays an important role in the training of specialists in higher education in physics and mathematics, since it combines mathematical theory of methods, the study of which requires fundamental mathematical knowledge and knowledge of the basics of programming and special mathematical packages. The principles of creation, editing of the integrated environment (M-books), methods of executing Matlab commands in the created environment are considered. As a result, text documents are created directly in the word processor Word, through which complex scientific and technical calculations are carried out. The Word and Matlab integrated environment is a client-server system in which Word is a client, while Matlab is a server. In this paper it is proposed to use two types of M-books for studying numerical methods, namely: for viewing and performing laboratory works. The structure of such M-books is proposed. The structure of M-books for the study and execution of laboratory works is developed. In the paper, the M-books of simple iteration and Newton's methods for the approximate solving of a nonlinear equation with one variable are presented, as well as the M-book studying quadrature formulas of central rectangles and trapezoids. The examples of these M-books show the benefits of using the integrated Word and Matlab environment for teaching computing methods, namely, in a text document, along with mathematical numerical-theory theory, there are Matlab commands for implementing the method. This allows the student, after completing each step of the algorithm, to analyze the results obtained.